2021
DOI: 10.1111/aec.13033
|View full text |Cite
|
Sign up to set email alerts
|

Bromeliad habitat regulates the richness of associated terrestrial and aquatic fauna

Abstract: Bromeliads harbour a great diversity of fauna species. The epiphytic habit of bromeliads is subject to higher temperatures and higher incidence of light than is the epigeic habit, so we expected individuals of the Vriesea neoglutinosa species to differ in terms of the composition, richness and abundance of their fauna associated with different bromeliad habits. We carried out a study in a restinga area on Marambaia Island, Brazil. We collected 32 bromeliads, of which 16 were epigeic and 16 were epiphytic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The potential for species to acclimate to higher temperatures needs to be investigated. The necessary contrivances of the experiment may have missed the gamma diversity (in a functional sense) present in tank-bromeliad communities (Laviski et al, 2021).…”
Section: T Lmentioning
confidence: 99%
“…The potential for species to acclimate to higher temperatures needs to be investigated. The necessary contrivances of the experiment may have missed the gamma diversity (in a functional sense) present in tank-bromeliad communities (Laviski et al, 2021).…”
Section: T Lmentioning
confidence: 99%
“…Due to the complexity of their structure, the bromeliads offer all those features found in this type of habitat (see Dias & Brescovit, 2004; Hernández‐Baz et al., 2011; Panizon et al., 2014). Previous studies indicated that bromeliads are biodiversity amplifiers and key elements in the structuring of communities (Gonçalves‐Souza, Brescovit, et al., 2010; Jorge et al., 2021; Laviski et al., 2021). The spiral arrangement of their leaves forms a rosette‐like structure that can store water and organic debris in the form of phytotelm (Cogliatti‐Carvalho et al., 2010; Islair et al., 2015; Kitching, 2001; Rocha, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that bromeliads are biodiversity amplifiers and key elements in the structuring of communities (Gonçalves-Souza, Brescovit, et al, 2010;Jorge et al, 2021;Laviski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%